Assessment of Cardiovascular Risk in Patients with Fatty Liver: Impact of Hepatic Cirrhosis - Arely Gayosso-Godinez; Raúl Contreras-Omaña (Annals of Hepatology)
Introduction and Objectives: According to the literature, cardiovascular events have been described as the leading cause of death in patients with fatty liver associated with metabolic dysfunction (MASLD). The main objective of this study is to assess and compare cardiovascular risk in two groups of patients: those diagnosed with fatty liver without cirrhosis and those with liver cirrhosis attributable to fatty liver. The aim is to determine if there is a significant difference in cardiovascular risk between these groups, identify the most relevant cardiovascular risk factors, and explore possible associations between progression to liver cirrhosis and increased cardiovascular risk. Materials and Patients: A retrospective cross-sectional study was conducted from 2020 to 2024, involving a total of 289 patients, of whom 165 were diagnosed with MASLD without cirrhosis and 125 patients were diagnosed with cirrhosis associated with fatty liver. In the first group, the grade of hepatic steatosis was determined by imaging methods, and cardiovascular risk assessment scales such as GLOBORISK and PREVENT were applied to both groups, conducting a comparative analysis between these study groups. Additionally, variables such as sex, age, weight, height, obesity, sedentary lifestyle, glomerular filtration rate, smoking, diabetes, hypertension, total cholesterol levels, LDL, HDL, and triglyceride levels were evaluated. Results: In the present study, 165 patients diagnosed with MASLD were evaluated using two cardiovascular assessment scales: PREVENT and GLOBORISK. According to the PREVENT scale, 86 patients (52.1%) exhibited a low cardiovascular risk, with 50.9% also showing mild hepatic steatosis confirmed by imaging studies. Using the GLOBORISK scale, it was determined that 117 patients (70.9%) had a low level of cardiovascular risk. On the other hand, a total of 124 patients with hepatic cirrhosis associated with fatty liver were included. According to the evaluation using the PREVENT scale, it was found that 64 patients (51.6%) had an intermediate cardiovascular risk, and according to the GLOBORISK model, 45 patients (36.2%) were classified with a moderate risk. When contrasting between the group of patients with cirrhosis and those with only fatty liver, the first group has a 3.6 times higher likelihood (OR 3.6) of presenting a moderate to severe cardiovascular risk compared to those without cirrhosis (P=0.00). Conclusions: This study demonstrates that patients with cirrhosis associated with fatty liver have a 3.6 times higher prevalence of moderate to severe cardiovascular risk compared to patients without cirrhosis but with fatty liver. This suggests a need for closer monitoring of cardiovascular events alongside liver disease monitoring.